Chronic Care Management and Diabetes Complications in Medicare Patients with Diabetes and Multiple Chronic Conditions - Mariétou H. Ouayogodé; Yingying Zheng (Population Health Management, 2026)
Chronic care management (CCM) services may improve disease management and reduce complications for chronically ill patients with multimorbidity. This retrospective study analyzed Medicare claims data (2015–2020) for diabetes patients with multimorbidity, with evaluation and management visits in four U.S. states (Illinois, Iowa, Minnesota, and Wisconsin). The authors assessed differences in diabetes complications among patients receiving CCM services (CCM patients) compared with those not receiving such services (non-CCM patients). The study described patients’ characteristics and diabetes-related complications by CCM receipt and identified the frequency of CCM service types (complex and noncomplex). Using propensity-score bounding, covariate and weight-adjusted probabilities of complications were compared across CCM and non-CCM patients. Heterogeneity in estimated probabilities was assessed across states and age categories. Of 5,465,138 visits analyzed, 38,403 visits included CCM services (with noncomplex CCM representing 95.4% of all CCM visits). Regression analyses showed that CCM patients had comparable estimated probability of developing neurological (0.048 vs. 0.046, P = 1.240) complications, lower probability of renal (0.014 vs. 0.017, P < 0.001) and ophthalmical (the least common complication, 0.009 vs. 0.010, P = 0.066) complications, but relatively higher probability of hypoglycemia (the most common complication, 0.070 vs. 0.061, P < 0.001) and circular/vascular (0.034 vs. 0.027 in non-CCM patients, P < 0.001 for the difference) complications than non-CCM patients. There were differences in estimated probability of complications across states and age categories. Non-complex CCM may not suffice to reduce the development of diabetes-related complications among diabetes patients with multimorbidity.